Association between genetic variations of NMDA receptor NR3 subfamily genes and heroin addiction in male Han Chinese. (19th September 2016) - Xie, Xiaohu; Liu, Huifen; Zhang, Jianbing; Chen, Weisheng; Zhuang, Dingding; Duan, Shiwei; Zhou, Wenhua
Highlights: This is the first report of the genetic risk factors associated with the NR3 gene in heroin addiction. Rs17189632 of GRIN3A and rs2240158 of GRIN3B are associated with heroin addiction. Some haplotypes at GRIN3A and at GRIN3B are associated with heroin addiction. Abstract: Growing amounts of evidence suggest that N-Methyl-d -aspartate (NMDA) receptor mediated glutamate neurotransmission may be involved in the pathophysiology of drug dependence. The NMDA receptor consists of three subfamilies (NR1, NR2, and NR3). The ability of subunit NR3 to negatively modulate the NMDA receptor function makes it an attractive candidate gene of heroin addiction. The purpose of this study is to explore the association between four single nucleotide polymorphisms (SNPs) of NR3 gene and heroin addiction. Genotyping of two SNPs (rs3739722 and rs17189632) in GRIN3A and two SNPs (rs4807399 and rs2240158) in GRIN3B was performed using TaqMan SNP genotyping method. The association between heroin addiction and these SNPs was assessed among 332 male heroin dependent patients and 400 male normal control subjects. The results showed the genotype and allele frequencies of rs17189632 and rs2240158 were significantly different between the cases and the controls (nominal P values were 0.0284, 0.0136 for rs17189632; 0.0048, 0.0013 for rs2240158, respectively). After Bonferroni correction, rs2240158 of GRIN3B was still found to be associated with heroin addiction. The frequencies of haplotype C-A at GRIN3A (rs3739722-rs17189632) and of C-C and C-T at GRIN3B (rs4807399-rs2240158) differed significantly between the cases and the controls. The genotype and allele distributions of rs3739722 and rs4807399 were not significantly different between in the cases and in the controls ( P  > 0.05). These results suggest that GRIN3A rs17189632 and GRIN3B rs2240158 may contribute to the susceptibility of heroin addiction.